2004
DOI: 10.1007/bf03191391
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake relocation and 3-dimensional crustal structure of P-wave velocity in cen-tral-western China

Abstract: A simultaneous inversion of earthquake relocation and three-dimensional crustal structure of P-wave velocity in central-western China (21°N~36°N, 98°E~112°E) were performed in this paper. The crustal P-wave velocity model and earthquake relocation for this region are obtained using P g and S g phase readings of 9 988 earthquakes from 1992 to 1999 recorded at 193 seismic stations within central-western China by SPHYPIT90 and SPHREL3D90 programs. A lateral inhomogeneous structure of P-wave velocity in this regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…In our research, 97.84 percent of aftershocks depth ranged from 0 km to 20 km. This result is consistent with other researches (Zhu et al, 2008;Huang et al, 2008;Chen et al, 2009;Yang et al, 2004).…”
Section: Results Of Double Difference Relocationsupporting
confidence: 96%
See 1 more Smart Citation
“…In our research, 97.84 percent of aftershocks depth ranged from 0 km to 20 km. This result is consistent with other researches (Zhu et al, 2008;Huang et al, 2008;Chen et al, 2009;Yang et al, 2004).…”
Section: Results Of Double Difference Relocationsupporting
confidence: 96%
“…The west of Longmenshan region is Songpan-Garze fold belt and east of the region is Sichuan Basin of which the crust is hard. Some researches (Yang et al, 2004) showed that earthquakes located in central and western regions of China usually happened in upper and middle of curst, and the depth of earthquake is no more than 20 km. In our research, 97.84 percent of aftershocks depth ranged from 0 km to 20 km.…”
Section: Results Of Double Difference Relocationmentioning
confidence: 99%
“…Travel time differences are predicted using a 1-D layered velocity model used for relocations in this study ( Table 1). The 1-D layered seismic wave velocity model used for predicting the travel time differences is based on previous studies of seismic wave velocity structure for the study region (Zhao et al, 1987(Zhao et al, , 1997Yang et al, 2004). This model is appropriate for the purpose for predicting the travel time differences because the DD algorithm is a relative earthquake location method which is much less dependent on the models, compared with "absolute" methods (Waldhauser and Ellsworth, 2000).…”
Section: Earthquake Relocationmentioning
confidence: 99%
“…Physical constants such as the P-wave velocity, Poisson's ratio, and the density, applied to each element are summarized in Table 2, where the Poisson's ratio and density are assumed to be constant. In the present study, we have constructed two P-wave velocity models, namely Models Vp-1 and Vp-2, taking into consideration the measured P-wave velocities of the boring core samples and a P-wave velocity model used for earthquake locations (Yang, Z.-X. et al, 2004) in order to check the effect of the difference of the velocity models.…”
Section: Effect Of Landscape Topography On the Stress State At Shallomentioning
confidence: 99%